Central cholinergic nervous system and cholinergic agents - Patocka, J (Acta medica (Hradec Kralove), 1998)
Central cholinergic nervous system play important role in many physiological and behavioral functions in humans. The activity of the cholinergic nervous system depends upon the production and fate of acetylcholine and all compounds influenced its biosynthesis, storage, release, hydrolysis, interaction with different subtypes of cholinergic receptors, etc., there are very important drugs and therapeutics. This paper summarizes current views on many compounds which can interact with different parts of central cholinergic nervous system.
Keywords: Cholinergic Agents; Cholinergic Fibers; acetylcholin; Animals; receptory cholinergní; cholinergní vlákna; lidé; zvířata; cholinesterasové inhibitory; Cholinesterase Inhibitors; Acetylcholine; Receptors, Cholinergic; cholinergní látky; Humans